Amplification and Quantitation of Telomeric Extrachromosomal Circles - Nathaniel Robinson; William Schiemann (Bio-Protocol, 2023)
Telomeres are structures that cap the ends of linear chromosomes and play critical roles in maintaining genome integrity and establishing the replicative lifespan of cells. In stem and cancer cells, telomeres are actively elongated by either telomerase or the alternative lengthening of telomeres (ALT) pathway. This pathway is characterized by several hallmark features, including extrachromosomal C-rich circular DNAs that can be probed to assess ALT activity. These so-called C-circles are the product of ALT-associated DNA damage repair processes and simultaneously serve as potential templates for iterative telomere extension. This bifunctional nature makes C-circles highly sensitive and specific markers of ALT. Here, we describe a C-circle assay, adapted from previous reports, that enables the quantitation of C-circle abundance in mammalian cells subjected to a wide range of experimental perturbations. This protocol combines the Quick C-circle Preparation (QCP) method for DNA isolation with fluorometry-based DNA quantification, rolling circle amplification (RCA), and detection of C-circles using quantitative PCR. Moreover, the inclusion of internal standards with well-characterized telomere maintenance mechanisms (TMMs) allows for the reliable benchmarking of cells with unknown TMM status. Overall, our work builds upon existing protocols to create a generalizable workflow for in vitro C-circle quantitation and ascertainment of TMM identity.